Azorhizobium caulinodans Transmembrane Chemoreceptor TlpA1 Involved in Host Colonization and Nodulation on Roots and Stems - Liu, Wei; Yang, Jinbao; Sun, Yu; Liu, Xiaolin; Li, Yan; Zhang, Zhenpeng; Xie, Zhihong (Frontiers in Microbiology, 2017)
Azorhizobium caulinodans ORS571 is a motile soil bacterium that interacts symbiotically with legume host Sesbania rostrata, forming nitrogen-fixing root and stem nodules. Bacterial chemotaxis plays an important role in establishing this symbiotic relationship. To determine the contribution of chemotaxis to symbiosis in A. caulinodans ORS571-S. rostrata, we characterized the function of TlpA1 (transducer-like protein in A. caulinodans), a chemoreceptor predicted by SMART (Simple Modular Architecture Research Tool), containing two N-terminal transmembrane regions. The tlpA1 gene is located immediately upstream of the unique che gene cluster and is transcriptionally co-oriented. We found that a ΔtlpA1 mutant is severely impaired for chemotaxis to various organic acids, glycerol and proline. Furthermore, biofilm forming ability of the strain carrying the mutation is reduced under certain growth conditions. Interestingly, competitive colonization ability on S. rostrata root surfaces is impaired in the ΔtlpA1 mutant, suggesting that chemotaxis of the A. caulinodans ORS571 contributes to root colonization. We also found that TlpA1 promotes competitive nodulation not only on roots but also on stems of S. rostrata. Taken together, our data strongly suggest that TlpA1 is a transmembrane chemoreceptor involved in A. caulinodans-S. rostrata symbiosis.